America's jihad: a history of origins - Parenti, Christian (Social justice, 2001)
The writer examines the role of the U.S. in nurturing the same Islamic military networks that are now the number one enemy worldwide, in an effort to understand America's war on terrorism. He contends that the American policy toward Islamic extremists, jihadists, was highly contradictory—the U.S. did not take the extremists' threats seriously because it found much of their activity useful.